Kritik terhadap Dikotomi Ilmu dalam Islam: Upaya Menyelaraskan Pengetahuan Agama dan Umum di Era Modern - Damayanti, Dita; Sodiman (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2024)
Knowledge is a fundamental human necessity that enables individuals to navigate various challenges in life. However, throughout history, a dichotomy has often been drawn between religious knowledge and secular knowledge, leading to a conceptual division of science. This dichotomy has had a detrimental impact on the intellectual and scientific development of the Muslim world, contributing to its decline in science and technology in comparison to the West. This stands in stark contrast to the Islamic Golden Age, during which Islamic civilization served as a center of knowledge and a beacon for Europe, which was then in a period of intellectual stagnation. This study aims to critically examine the dichotomy of knowledge within Islamic thought and to explore integrative solutions for Islamic education in the modern era. Employing a qualitative method through library research, this study reveals that for Islamic education to meet the demands of an increasingly dynamic and globalized world, a balanced integration of religious and secular knowledge is essential. Thus, in addition to understanding religious principles, learners must also acquire practical knowledge and skills applicable to everyday life and relevant to the global labor market.